Alley activation: genius loci to construct a resilient city - Nur, Khilda Wildana (Journal of Architecture and Urbanism, 2020)
Alleys in urban areas have recently been associated with crime and slums. Makassar as one of the biggest cities in Indonesia started to revitalize its alleys in 2014 as a campaign agreement implemented in Makassar Spatial Plan as well as an urban mutual interaction. This scheme is to change negative perspectives about alleys and to enhance urban community awareness. The research is a qualitative method with a phenomenological paradigm referring to urban design toolkits. Data collecting uses observation surveys and walk-through analyses. The selected alleys that have been discussed are based on thematic alleys from the government decisions. The findings show that successful government programs should empower the inheritance of cultural values. Genius loci adapted from the local nomenclature programs are more recognizable in public to build sense of belonging and promote urban resilience. The revitalization of alleys provide communal space, urban farming harvest, and leads to green economy improvements, settlement arrangements, and mutual local aids. Constructing urban resilience through government programs that should not depend on a Mayor’s tenure is another finding in this research. Adaptive governance is essential in flexible and collaborative management rather than application programs in terms of political interests, beautification, and ceremonial activities.